The Aftermath Implications of Teenage Pregnancy on the Girl Child Education - Odiri, Onoshakpokaiye E; Anthonia, Oboawharhe Eloho (COUNS-EDU: The International Journal of Counseling and Education, 2023)
The aim of the study is to investigate: i) impact of teenage pregnancy on the girl child attending government secondary schools ii) the level of academic accomplishment of the pregnant teenagers at the public secondary schools. The research design for this study was a descriptive survey. The study population made up of 800 teen mothers. A sample of 200 teen mothers in Ethiope East Local Government Area of Delta State, Nigeria, who had dropped out of secondary school as a result of teen pregnancies, was chosen through simple random sampling. The instrument utilized to collect the data was questionnaire which was administered to the participants, validated by three experts and its reliability was tested using Cronbach alpha which yielded 0.68. The participants were also interviewed. The data collected were analyzed using simple percentages. The results showed that young women who became pregnant while in school face a variety of difficulties, including early marriage, rejection by the family, disassociation from former classmates, social isolation, frequent absences following pregnancies, poor academic performance, and reasons for dropping out of school. The findings revealed that teen pregnancies affect the relationship of the girl child, family and peer group and also have an impact on young girls' academic performance in public secondary schools. We deduced from the literature review that adolescent pregnancy is a widespread problem that demands attention due to its effects on the education of girls. Some recommendations were also made.